Amino-acid modulated hierarchical In/H-Beta zeolites for selective catalytic reduction of NO with CH4 in the presence of H2O and SO2. Issue 15 (4th April 2022) - Zhao, Jiuhu; Dong, Lei; Wang, Yungang; Zhang, Jingwen; Zhu, Rongshu; Li, Chaolin; Hong, Mei
Abstract : Mesoporous In/H-Beta-P synthesized using proline exhibits the highest NO x removal efficiency and stability in excess oxygen and poisonous SO2 and H2 O. Abstract : Selective catalytic reduction of NO with CH4 (CH4 -SCR) has been studied over a series of amino-acid mediated hierarchical beta zeolites with indium exchange. Amino acid mesoporogens greatly affect the NO reduction (DeNO x ) efficiency of In/H-Beta catalysts. Mesoporous In/H-Beta-P synthesized using proline exhibits the highest NO x removal efficiency of 40% in excess oxygen and poisonous SO2 and H2 O, 10% higher than our previously optimized In/H-Beta catalyst using commercial beta zeolites with a similar Si/Al ratio. Analyses using XRD, N2 adsorption–desorption, EPR, SEM, TEM, EDX, ICP, 27 Al and 29 Si MAS NMR, XPS, H2 -TPR, NH3 -TPD, and Py-IR reveal that amino acids promote beta crystallization, modulate zeolite acid sites and surface oxygen species, and generate hierarchical pore architectures without affecting the Si/Al ratio, indium content, and percentage of the active InO + species. The mosaic-structured In/H-Beta-P exhibits the strongest Brønsted acidity and surface labile oxygen which enhance the oxyindium interaction with the zeolite framework, promoting CH4 -SCR activity. The strong acidity, surface active oxygen species, and mesopores lead to excellent stability of the In/H-Beta-P catalyst in the presence of SO2 and H2 O, withstanding several catalytic DeNO x cycles under harsh reaction conditions.